Computing and Combinatorics 16th Annual International Conference, COCOON 2010, Nha Trang, Vietnam, July 19-21, 2010. Proceedings - Thai, My T.; Sahni, Sartaj; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the 16th Annual International Conference on Computing and Combinatorics, held in Nha Trang, Vietnam, in July 2010.
Invited Talks -- Understanding and Inductive Inference -- Computing with Cells: Membrane Systems -- Complexity and Inapproximability -- Boxicity and Poset Dimension -- On the Hardness against Constant-Depth Linear-Size Circuits -- A K-Provers Parallel Repetition Theorem for a Version of No-Signaling Model -- The Curse of Connectivity: t-Total Vertex (Edge) Cover -- Counting Paths in VPA Is Complete for #NC 1 -- Depth-Independent Lower Bounds on the Communication Complexity of Read-Once Boolean Formulas -- Approximation Algorithms -- Multiplying Pessimistic Estimators: Deterministic Approximation of Max TSP and Maximum Triangle Packing -- Clustering with or without the Approximation -- A Self-stabilizing 3-Approximation for the Maximum Leaf Spanning Tree Problem in Arbitrary Networks -- Approximate Weighted Farthest Neighbors and Minimum Dilation Stars -- Approximated Distributed Minimum Vertex Cover Algorithms for Bounded Degree Graphs -- Graph Theory and Algorithms -- Maximum Upward Planar Subgraph of a Single-Source Embedded Digraph -- Triangle-Free 2-Matchings Revisited -- The Cover Time of Deterministic Random Walks -- Finding Maximum Edge Bicliques in Convex Bipartite Graphs -- A Note on Vertex Cover in Graphs with Maximum Degree 3 -- Computing Graph Spanners in Small Memory: Fault-Tolerance and Streaming -- Factorization of Cartesian Products of Hypergraphs -- Graph Drawing and Coloring -- Minimum-Segment Convex Drawings of 3-Connected Cubic Plane Graphs -- On Three Parameters of Invisibility Graphs -- Imbalance Is Fixed Parameter Tractable -- The Ramsey Number for a Linear Forest versus Two Identical Copies of Complete Graphs -- Computational Geometry -- Optimal Binary Space Partitions in the Plane -- Exact and Approximation Algorithms for Geometric and Capacitated Set Cover Problems -- Effect of Corner Information in Simultaneous Placement of K Rectangles and Tableaux -- Detecting Areas Visited Regularly -- Tile-Packing Tomography Is -hard -- The Rectilinear k-Bends TSP -- Tracking a Generator by Persistence -- Auspicious Tatami Mat Arrangements -- Automata, Logic, Algebra and Number Theory -- Faster Generation of Shorthand Universal Cycles for Permutations -- The Complexity of Word Circuits -- On the Density of Regular and Context-Free Languages -- Extensions of the Minimum Cost Homomorphism Problem -- The Longest Almost-Increasing Subsequence -- Universal Test Sets for Reversible Circuits -- Approximate Counting with a Floating-Point Counter -- Network Optimization and Scheduling Algorithm -- Broadcasting in Heterogeneous Tree Networks -- Contention Resolution in Multiple-Access Channels: k-Selection in Radio Networks -- Online Preemptive Scheduling with Immediate Decision or Notification and Penalties -- Computational Biology and Bioinformatics -- Discovering Pairwise Compatibility Graphs -- Near Optimal Solutions for Maximum Quasi-bicliques -- Fast Coupled Path Planning: From Pseudo-Polynomial to Polynomial -- Constant Time Approximation Scheme for Largest Well Predicted Subset -- On Sorting Permutations by Double-Cut-and-Joins -- A Three-String Approach to the Closest String Problem -- A 2k Kernel for the Cluster Editing Problem -- Data Structure and Sampling Theory -- On the Computation of 3D Visibility Skeletons -- The Violation Heap: A Relaxed Fibonacci-Like Heap -- Threshold Rules for Online Sample Selection -- Heterogeneous Subset Sampling -- Cryptography, Security, Coding and Game Theory -- Identity-Based Authenticated Asymmetric Group Key Agreement Protocol -- Zero-Knowledge Argument for Simultaneous Discrete Logarithms -- Directed Figure Codes: Decidability Frontier.
Keywords: Computer science; Computer Communication Networks; Computer software; Computational complexity; Artificial intelligence; Computer graphics; Computer Science; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Computer Communication Networks; Computation by Abstract Devices; Computer Graphics; Artificial Intelligence (incl. Robotics).